Kojenie obrazem, leczenie snem. Konstruowanie pamięci o Zagładzie w polskich filmach fabularnych po 1989 roku - Forecki, Piotr (Wydawnictwo Naukowe WNPiD UAM, 2012)
In the period between the end of World War II and the late 1980s the Polish film industry produced nearly twenty films on the Holocaust which approached the topic within secure lim- its. Those films that were permitted to be shown did not disturb the good feeling of the na- tional community, did not refer to the Polish version of anti-Semitism, and first and foremost avoided the sensitive issue of Polish society’s attitude to the annihilation of the Jews. Each film complied with the then current historical policy, which either treated this issue instru- mentally or simply ignored it. After 1989, both historiography and cinematography began to fill in the blank spots and address topics that were formerly forbidden, taboo or distorted in the official state discourse. Due to the abolishment of political restrictions and the liberation of public discourse, Polish cinematography embarked upon a belated examination of conscience and revision of the memories of the Holocaust cultivated till then. At least it seemed so. Has it actually happened, though? Have Polish filmmakers actually taken the trouble to deconstruct the myths, fill in the gaps and correct the deformed Polish memories of the Holocaust? Even if the answers to these superficial questions are affirmative, at least in terms of their intentions, what has become of it? This paper is an attempt to identify how the memory of the Holocaust has been constructed in Polish feature movies since 1989.
Soothing with Pictures, Curing with Dreams. The Construction of the Memory of the Holocaust in Polish Feature Films after 1989
Keywords: pamięć; film fabularny; historia